Detection and characterization of Hyaloklossia kasumiensis (Apicomplexa: Sarcocystidae) from Nagoya Daruma pond frog, Pelophylax porosus brevipodus. (October 2022) - Tokiwa, Toshihiro; Kezuka, Chiho; Yamada, Shoto; Chou, Shyun; Nakamura, Shin-ichi
Abstract: The Nagoya Daruma pond frog ( Pelophylax porosus brevipodus ) is an endangered anuran species endemic to the semi-aquatic environment of Japan. On June 11, 2021, four of the six Nagoya Daruma pond frogs captured from the wild and kept in an aquarium died in rapid succession. Pathological and/or parasitological examinations of two of the four carcasses revealed protozoan infection in their kidneys. The pathogen identified as Hyaloklossia kasumiensis (Apicomplexa: Sarcocystidae: Hyaloklossiinae) based on their morphological and molecular characterization. This is a new host record of H. kasumiensis. Mitochondrial cox1 sequence analysis suggest that the present species detected from Nagoya Daruma pond frog belongs to the same lineage as those found in the Tokyo Daruma pond frog ( P. p. porosus ) from Ibaraki Prefecture, Japan. This particular lineage may be prevalent among Pelophylax porosus ssp. distributed in Japan. Graphical abstract: Unlabelled Image Highlights: Six wild-caught Nagoya Daruma pond frogs were kept in a aquarium. Of the four frogs that died, two have protozoan infection in their kidneys. The pathogen was identified as Hyaloklossia kasumiensis . This is the first description of H. kasumiensis in Nagoya Daruma pond frogs. Hyaloklossia is assumed to be widespread among Pelophylax species in Japan.